2010
DOI: 10.1152/ajpregu.00373.2009
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte responses exacerbate angiotensin II-dependent hypertension

Abstract: cyte responses exacerbate angiotensin II-dependent hypertension. Am J Physiol Regul Integr Comp Physiol 298: R1089-R1097, 2010. First published February 10, 2010 doi:10.1152/ajpregu.00373.2009.-Activation of the immune system by ANG II contributes to the pathogenesis of hypertension, and pharmacological suppression of lymphocyte responses can ameliorate hypertensive end-organ damage. Therefore, to examine the mechanisms through which lymphocytes mediate blood pressure elevation, we studied ANG II-dependent hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
149
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 70 publications
9
149
0
4
Order By: Relevance
“…It was Guzik et al who observed that mice lacking T cells are resistant to the development of both Ang II and deoxycorticosterone acetate-salt induced hypertension, and adoptive transfer of T cells, but not B cells, restored hypertension in these mice. 3 Despite this investigation and others 29,30 considerably improving our understanding of the adaptive immune system in the pathogenesis of hypertension and vascular dysfunction, there are still gaps in knowledge surrounding how it is signaled for involvement in the first place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was Guzik et al who observed that mice lacking T cells are resistant to the development of both Ang II and deoxycorticosterone acetate-salt induced hypertension, and adoptive transfer of T cells, but not B cells, restored hypertension in these mice. 3 Despite this investigation and others 29,30 considerably improving our understanding of the adaptive immune system in the pathogenesis of hypertension and vascular dysfunction, there are still gaps in knowledge surrounding how it is signaled for involvement in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…3,29,30 T cells also have a central role in the development of autoimmune disorders, and as a result, loss of immunological tolerance has been proposed as an underlying factor in hypertension. 36 Interestingly, CQ and other antimalarial agents have long been used as therapeutic agents in the treatment of autoimmune conditions (e.g., rheumatoid arthritis and systemic lupus erythematosus 37,38 ), even though their precise mechanism(s) of action are still not known.…”
Section: Discussionmentioning
confidence: 99%
“…These results have been confirmed in severe combined immunodeficiency mice and in Dahl salt-sensitive rats in which the RAG-1 or the essential T cell receptor component CD3 have been deleted using zinc finger nuclease technology. [4][5][6] This seminal work has caused great interest in the immunologic aspects of hypertensive disease. [7][8][9][10] This review will give a brief overview of the components of the innate and adaptive arm of the immune system in hypertension and summarize recent advances in immunologic research, with a special focus on their potential relevance for hypertension and hypertensive endorgan damage.…”
mentioning
confidence: 99%
“…1,2 More recently, we have shown that RAG1 −/− mice, which lack mature T and B lymphocytes, are protected from severe angiotensin II-induced or deoxycorticosterone acetatesalt hypertension and vascular damage. 4 Similar findings were confirmed in mice with severe combined immunodeficiency, 5 and more recently in RAG1 −/− Dahl salt-sensitive rats, which were protected from salt-sensitive hypertension, heart hypertrophy, and renal damage. 6 These hypertensive phenotypes are dependent on T-cell activation.…”
mentioning
confidence: 64%